Pre-service English teachers’ beliefs toward the teaching English grammar - Sibarani, Sharon Sion; Hendriwanto; Nurjannah, Nunung (Research and Innovation in Language Learning, 2025)
Numerous studies have been conducted to investigate the beliefs of pre-service teachers in teaching grammar in English education. This study, is located in a university of education in Cirebon, explores pre-service English teacher beliefs in teaching grammar since their beliefs could shape how they teach in the future. To understand the knowledge gap of pre service teachers’ beliefs to teach grammar, the study employed an interpretive paradigm, qualitative approach, case study design, thematic analysis, and purposive sampling. Data was generated using semistructured interviews. The research findings indicate that pre-service teachers do perceive grammar as challenging, but nonetheless, they believe that grammar is crucial to master. The beliefs of pre-service teachers in teaching grammar are influenced by their schooling experiences, where positive experiences foster confidence and self-assurance, whereas negative experiences lead to self-doubt. Despite the varying learning experiences in grammar found in this study, both participants believe that to provide effective instruction to students, pre-service teachers need to have a well-balanced blend of pedagogical knowledge and grammatical knowledge.